Collagen type-I A2 gene polymorphisms and susceptibility to intracranial aneurysms: a meta-analysis of genetic association studies. (3rd July 2018) - Brotis, Alexandros G.; Tasiou, Anastasia; Giannis, Theofanis; Paschalis, Athanasios; Fountas, Kostas N.
ABSTRACT: Background: The development, evolution and rupture of intracranial aneurysms are in part related to genetic factors. The role of collagen type-I a2 genetic polymorphisms has not been clarified yet. Material and methods: A meta-analysis was realized by means of a genotype model-fitting process (allele contrast, recessive, dominant, additive and co-dominant), and a model-free approach using the generalized odds ratio. The latter was assessed in association to the degree of dominance ( h -index). Results: No statistically significant association was documented between EX28 G>C collagen type-I a2 variant and intracranial aneurysms (generalized odds ratio = 1.23, 95% confidence interval = 0.57, 2.63). Significant associations between INT46 T>G collagen type I a2 variant and intracranial aneurysms were documented in three models, the dominant [0.52 (0.38, 069)], the co-dominant [0.50 (0.32, 0.78)] and the allele contrast models [0.63 (0.49, 0.82)]. The generalized odds ratio was estimated to be as high as 1.94 (1.23, 3.06). The degree of dominance ( h -index = −1.54) indicated that the TG genotype was characterized by lower risk of developing intracranial aneurysms compared to the TT genotype. Conclusions: The available literature data demonstrated that there is no association of collagen type-(2a) and intracranial aneurysms, through EX28 G>C (rs42524) polymorphism according to the model-fitting process and the model-free approach. Regarding the INT46 T>G (rs2621215) polymorphisms, the latter models indicated that there could be a protective effect of the G-allele against the development of intracranial aneurysms. However, the majority of studies are from East Asia, therefore the results are applicable primarily to that patient population.